TINJAUAN BIOKIMIA ENZIM INVERTASE PADA HIDROLISIS SUKROSA: Mekanisme Katalitik, Kinetika, Faktor Fisikokimia, dan Implikasi Aplikatif - Cahya Ariyanto, Piola; Linatusifa Febrianti; Maulinda Dwi Lestari; Elya Risma Nurdiana (Journal of Research and Education Chemistry, 2026)
Invertase (beta-fructofuranosidase; EC 3.2.1.26) is an enzyme that catalyzes the hydrolysis of sucrose into glucose and fructose and plays a crucial role in carbohydrate metabolism, fermentation, the food industry, and biotechnology. This review article synthesizes studies on invertase classification, the sucrose hydrolysis reaction, the catalytic mechanism, the Michaelis-Menten kinetic model, the determination of kinetic parameters such as Km, Vmax, kcat, and activation energy, as well as the influence of physicochemical factors such as pH, temperature, metal ions, inhibitors, and enzyme shape on its activity and stability. In general, invertase belongs to the glycoside hydrolase family 32 and operates through a retaining double-displacement mechanism involving aspartate and glutamate residues in the active site. Changing substrate concentration increases the reaction rate to near Vmax, but real-world systems can deviate due to substrate inhibition, product inhibition, diffusion barriers, and the influence of the reaction matrix. Increasing temperature increases the reaction rate constant up to the optimum temperature, but excessive temperatures cause denaturation and deviation from the Arrhenius model. Most invertases exhibit an optimum pH in the weak acid range, although alkaline invertases and low-temperature active invertases with different characteristics exist. Various analytical methods, such as DNS, Nelson-Somogyi, Bradford, chromatography, SDS-PAGE, as well as spectroscopic and crystallographic approaches, have been used to assess the activity, purity, and molecular properties of invertases. Overall, this review demonstrates that invertase performance is a result of the interaction between protein structure, reaction conditions, and the chemical environment. Therefore, an integrated understanding of these aspects is essential for optimizing laboratory and industrial applications(Manoochehri et al., 2020 ; Lammens et al., 2009 ; Potrich & Amaral, 2018). Keywords: invertase, sucrose, hydrolysis, enzyme kinetics, physicochemical factors